The representation of getting ill in adolescents with systemic lupus erythematosus - Resende,Ondina Lúcia Ceppas (2016)
ABSTRACT Introduction: This study, developed in a federal hospital in the city of Rio de Janeiro, has aimed to analyze the social representation of chronic disease and its treatment, in the perspective of adolescents and their caregivers. Methods: The sample consisted of 31 adolescents (11–21 years) with systemic lupus erythematosus and 19 caregivers (32–66 years), followed in the pediatrics and in the internal medicine outpatient clinics for a period of six months. Data was collected from the free association of words test, using chronic disease and treatment of chronic disease impulses, and later submitted to the Multiple Correspondence Analysis using the R software. Results: The group of adolescents associated the impulse chronic disease with the words medication, bad, illness, difficulty, no cure, faith and joy; and in the group of caregivers, to care, treatment, no cure and the word ‘no’. The impulse treatment of chronic disease was associated, in the group of adolescents, with the words patience, improvement, help, affection, care and bad; and in the group of caregivers, to caring, hope, schedule, knowledge, obedience, medication, professional and improvement. Caregivers also associated impulses and words according to age: chronic disease was associated with the word care (over 61 years), pain and impotence (42–61 years), treatment (22–41 years); and treatment of chronic disease, with the words strength (over 61 years), professional, knowledge and improvement (42–61 years), affection and schedule (22–41 years). Conclusions: Considering as subjective and dynamic the experience of getting ill, knowing the representations can contribute to the orientation of conduct and type of psychotherapeutic intervention needed.